2022
DOI: 10.1600/036364422x16512564801614
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Studies on Malagasy Dalbergia (Fabaceae). III. Two New Species from Southeastern Madagascar and an Emended Description of the Rosewood Species Dalbergia maritima

Abstract: Abstract— The Malagasy rosewood species Dalbergia maritima has a long history of unsustainable exploitation for its beautiful, burgundy-colored heartwood. As currently circumscribed, D. maritima has a wide geographic distribution in eastern Madagascar and exhibits significant morphological, ecological, and genetic variation, suggesting it may comprise more than a single entity. Multivariate analyses of leaf, flower, and inflorescence characters as well as eco-geographic features reveal several morphologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…The recent studies performed on Malagasy members of this genus concur with our phylogenetic analyses in that supergroup 1 includes D. tricolor, D. chapelieri, D. pervillei, D. maritima, and D. normandii and supergroup 2 comprises D. monticola, D. peltieri, D. trichocarpa, D. bemarivensis, D. chlorocarpa, D. lemurica, and D. baronii (Crameri, 2020). Our results are consistent with and complementary to previous studies by Crameri (2020) andHassold et al (2016) regarding the phylogenetic position of the 12 species analyzed herein.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The recent studies performed on Malagasy members of this genus concur with our phylogenetic analyses in that supergroup 1 includes D. tricolor, D. chapelieri, D. pervillei, D. maritima, and D. normandii and supergroup 2 comprises D. monticola, D. peltieri, D. trichocarpa, D. bemarivensis, D. chlorocarpa, D. lemurica, and D. baronii (Crameri, 2020). Our results are consistent with and complementary to previous studies by Crameri (2020) andHassold et al (2016) regarding the phylogenetic position of the 12 species analyzed herein.…”
Section: Discussionsupporting
confidence: 93%
“…Our phylogenetic trees can also be used for differentiating species with ITS and in combination with rbcL . Our analyses confirm that the species of Malagasy Dalbergia are divided into two distinct groups (Crameri, 2020; Hassold et al, 2016; Vatanparast et al, 2013). The recent studies performed on Malagasy members of this genus concur with our phylogenetic analyses in that supergroup 1 includes D. tricolor , D. chapelieri , D. pervillei , D. maritima , and D. normandii and supergroup 2 comprises D. monticola , D. peltieri , D. trichocarpa , D. bemarivensis , D. chlorocarpa , D. lemurica , and D. baronii (Crameri, 2020).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The use of morphological keys for identification of Dalbergia species is challenging due to co‐occurrence of large numbers of closely related species leading to taxonomic uncertainties which has resulted in several revisions of genus (Crameri et al 2022). Ambiguity in species identification can have significant implications in National and International trade regulations and hamper strategizing conservation priorities.…”
Section: Discussionmentioning
confidence: 99%
“…International de mand has been primarily for rosewood (Mason et al, 2016), whereas in Madagascar, palisander has mostly served the needs of the local market (Rasamoelina, 2001). The taxonomic identity of the Dalbergia species that have been most heavily exploited in Madagascar is largely unknown (Mason et al, 2016), although the highest quality rosewood reportedly comes from the east ern part of the island (Normand, 1988;Ratsimbazafy et al, 2016;Crameri et al, 2022a) and notably from the southern half of the Masoala Peninsula, where precious woods were exploited extensively in the 1960s (Schuur man & Lowry, 2009). Minimum quantitative estimates (Ratsimbazafy et al, 2016) indicated that 152,437 tons of rosewood (corresponding to about 350,430 trees) were harvested in the period between 1991 and 2014, of which 104,655 tons (ca.…”
mentioning
confidence: 99%